Dangerous liaisons: gender, nation and postcolonial perspectives - McClintock, Anne; Shohat, Ella; Mufti, Aamir Rashid (Cultural politics, 1997)
This collection addresses the issues raised by the postcolonial condition, considering nationhood, history, gender and identity from an interdisciplinary perspective.
Keywords: LGBTQIA2+; approches et analyses; arts; cours; discipline; discours dominant; féminisme décolonial; histoire et politique; identités LGBTQIA2+; intersectionnalité; inégalités; lit4700; militance; poésie; premier cycle; queer; racisme; sexisme; systèmes d'oppressions; thématiques; études culturelles; études littéraires

Sisters in the struggle - Brand, Dionne; Stikeman, Ginny (1991)
Ce documentaire présente des femmes noires actives en politique ainsi que dans l'organisation communautaire, syndicale et féministe. Ils partagent leurs idées et leurs témoignages personnels sur le double héritage du racisme et du sexisme, liant leurs luttes personnelles à la bataille en cours pour mettre fin à la discrimination systémique et à la violence contre les femmes et les personnes de couleur.
Keywords: amériques; approches et analyses; canada; cours; fem3300; militance; premier cycle; racisme; ressource en ligne; régions géographiques; sexisme; systèmes d'oppressions; thématiques; violences

Mapping the margins: Intersectionality, identity politics, and violence against women of color - Crenshaw, Kimberlé William (Stanford Law Review, 1991)
Contemporary feminist and antiracist discourses have failed to consider the intersections of racism and patriarchy. To overcome this difficulty, an original approach is suggested here: that of intersectionality. In the first part, the paper discusses structural intersectionality, the ways in which the location of women of color at the intersection of race and gender makes their real experience of domestic violence, rape, and remedial reform qualitatively different from that of white women. The focus is shifted in the second part to political intersectionality, with the analysis of how both feminist and antiracist politics have functioned in tandem to marginalize the issue of violence against women of color. Finally, the implications of the intersectional approach are addressed within the broader scope of contemporary identity politics.
Keywords: 1900-1999; OFDIG; afro-féminisme; amériques; antiracisme; approches et analyses; cours; cycles supérieurs; fem9000; femmes* afro-américaines; féminismes noirs; incontournable; intersectionnalité; militance; patriarcat; périodes historiques; racisme; ressource en ligne; régions géographiques; systèmes d'oppressions; thématiques; violences; violences contre les femmes*; violences raciales; états-unis

Demarginalizing the intersection of race and sex: A black feminist critique of antidiscrimination doctrine, feminist theory and antiracist politics - Crenshaw, Kimberle (The University of Chicago Legal Forum, 1989)
Keywords: afro-féminisme; amériques; antiracisme; approches et analyses; cours; discipline; droit; féminismes noirs; incontournable; intersectionnalité; militance; pol4212; premier cycle; projet charge mentale; racisme; ressource en ligne; régions géographiques; science politique et droit; systèmes d'oppressions; thématiques; états-unis

Margaret Thatcher is my sister: Counselling on divisions between women - Itzin, Catherine (Women's Studies International Forum, 1985)
This paper looks at the ways in which women are divided from themselves and each other as women: at the internalised oppression which results from THE oppression of patriarchy, at the systematic mistreatment of women as a group by men as a group reinforced by the social structures of male power. It also looks at the ways in which women are divided from each other as a result of other oppressive systems such as class and/or race or religion or physical ability or age. The paper then describes how the particular theory and practice of Re-evaluation Counselling can be used to ‘deconstruct’ or ‘discharge’ the internalised oppression of patriarchy and other oppressive systems, making the principles of Women's Liberation and sisterhood a practical possibility for ‘everywoman’ and all women—including Margaret Thatcher. Throughout, the word ‘patriarchy’ is used to mean the system of male power usually regarded as synonymous with sexism.
Keywords: approches et analyses; capacitisme; militance; patriarcat; racisme; sororité; systèmes d'oppressions; thématiques; âgisme

Resistance to oppression: Black women's response to slavery in the united states - Ellison, Mary (Slavery & Abolition, 1983)
Keywords: afro-féminisme; amériques; approches et analyses; cours; esclavagisme; fem3100; femmes* afro-américaines; féminisme afroaméricain; histoire et politique; militance; premier cycle; racisme; régions géographiques; sexisme; systèmes d'oppressions; thématiques; violences; états-unis

Je suis une maudite sauvagesse = Eukuan nin matshimanitu innu-iskueu - Antane Kapesh, An (Leméac, 1976)
An Antane Kapesh signe un réquisitoire accablant contre les Blancs : « Quand le Blanc a voulu exploiter et détruire notre territoire, il n'a demandé de permission à personne, il n'a pas demandé aux Indiens s'ils étaient d'accord. »
Keywords: amériques; approches et analyses; autochtones; cours; discipline; fem1000; fem3100; femmes* innues; féminisme décolonial; littérature; manifeste; militance; pol4105; pol5480; premier cycle; premières nations; québec; racisme; racisme systémique; régions géographiques; systèmes d'oppressions; thématiques; études littéraires